The Impacts of Aligned Teaching on Students Perceived Engagement in Independent Learning and Satisfaction : An Empirical Investigation in Hong Kong (Global Journal of Human-Social Science, 2013)
In response to the move towards Outcomes-based Education in Hong Kong, our paper aims at investigating the impacts of the Outcomes-based Teaching and Learning approach (OBTL) on students' satisfaction and perceived engagement in independent learning in the context of higher education. Building upon the principle of "constructive alignment", we propose a theoretical model to examine the impacts of constructively aligned teaching and learning that is conceptualized as the constructive alignment Index in our paper. An empirical study of undergraduate students (n=253) found that the constructive alignment index (CAI) positively predicted students' satisfaction and their perceived engagement in independent learning. Implications for research and practice are discussed.
Keywords: outcomes-based teaching and learning; OBTL; outcomes-based education; OBE; constructive alignment; satisfaction; independent learning